Application Value of PET/CT and MRI in the Diagnosis and Treatment of Patients With Synchronous Multiple Pulmonary Ground-Glass Nodules - Xie, Shaonan; Li, Shaoteng; Deng, Huiyan; Han, Yaqing; Liu, Guangjie; Liu, Qingyi (Frontiers in Oncology, 2022)
Abstract Background: Synchronous multiple ground-glass nodules (SMGGNs) in synchronous multiple lung cancers are associated with specific imaging findings. It is difficult to distinguish whether multiple nodules are primary tumors or metastatic lesions in the lungs. The need for PET/CT and contrast-enhanced brain MRI for these patients remains unclear. This study investigated the necessity of these two imaging examinations for SMGGN patients by means of retrospective analysis. Methods: SMGGN patients who were diagnosed and treated in our hospital from October 2017 to May 2020 and underwent whole-body PET/CT and/or contrast-enhanced brain MRI were enrolled in this study. We analyzed the imaging and clinical characteristics of these patients to evaluate SMGGN patients’ need to undergo whole-body PET/CT and brain MRI examination. Results: A total of 87 SMGGN patients were enrolled. 51 patients underwent whole-body PET/CT examinations and did not show signs of primary tumors in other organs, metastatic foci in other organs, or metastasis to surrounding lymph nodes.87 patients underwent whole-brain MRI, which did not reveal brain metastases but did detect an old cerebral infarction in 23 patients and a new cerebral infarction in one patient. 87 patients underwent surgical treatment in which 219 nodules were removed. All nodules were diagnosed as adenocarcinoma or atypical adenomatous hyperplasia. No lymph node metastasis was noted. Conclusion: For SMGGN patients, a whole-body PET/CT examination is not necessary before surgery. Contrast-enhanced brain MRI can assess the patient’s cerebrovascular function before surgery and reduce the risk of perioperative cerebrovascular accidents. Thus, it is a necessary examination. Keywords: synchronous multiple ground-glass nodules (SMGGNs); positron-emission tomography and computed tomography (PET/CT); magnetic resonance imaging (MRI); adenocarcinoma